Pengaruh Motivasi Kerja, Kreativitas Dan Lingkungan Kerja Terhadap Kinerja Guru Di Sekolah Menengah Kejuruan Bina Nusa Kabupaten Bekasi - Sari , Novia; Ramli Zakaria , Teuku; Thaha , Abas (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2024)
The aim of this research is to determine the influence of work motivation, creativity and work environment on teacher performance at Bina Nusa Vocational School, Bekasi Regency. The method used in this research is a quantitative method, with analytical techniques of validity testing, reliability testing, classical assumption testing, multiple linear regression testing. The data collection technique in this research was a questionnaire, the sample used was 33 respondents, namely the entire population. The results of this research are: 1) Partially there is a positive and significant influence of work motivation variables on teacher performance at Bina Nusa Vocational School, Bekasi Regency with a calculated t value of 3.182 and a significance of 0.003, 2) Partially creativity has a positive and significant effect on teacher performance at Vocational Schools. Bina Nusa, Bekasi Regency with a calculated t value of 5.428 and a significance of 0.000, 3) Partially the Work Environment has a positive and significant effect on teacher performance at Bina Nusa Vocational School, Bekasi Regency with a calculated t value of 8.442 and a significance of 0.000, 4) Simultaneously Work Motivation , Creativity and Work Environment have a positive and significant effect on teacher performance at Bina Nusa Vocational School, Bekasi Regency with a calculated F value of 23.056 and a significance of 0.000. With a coefficient of determination value of 0.674, which means that the influence of the independent variables (Work Motivation, Creativity and Work Environment) on the dependent variable Y (Teacher Performance) is 67.4%, while the remaining 32.6% is influenced by other variables not examined in this research.